Ultrashort single-pulse laser ablation of stainless steel, aluminium, copper and its dependence on the pulse duration - Winter, Jan; Spellauge, Maximilian; Hermann, Jens; Eulenkamp, Constanze; Huber, Heinz P.; Schmidt, Michael (Optics Express, 2021)
In this work, we investigate single-pulse laser ablation of bulk stainless steel (AISI304), aluminium (Al) and copper (Cu) and its dependence on the pulse duration. We measured the reflectivity, ablation thresholds and volumes under the variation of pulse duration and fluence. The known drop of efficiency with increasing pulse duration is confirmed for single-pulse ablation in all three metals. We attribute the efficiency drop to a weakened photomechanically driven ablation process and a stronger contribution of photothermal phase explosion. The highest energetic efficiency and precision is achieved for pulse durations below the mechanical expansion time of 3-5 ps, where the stress confinement condition is fulfilled.
CRIS-Team Scopus Importer:2021-05-21